Magnetic, magnetodielectric, and magnetocaloric properties of new polar oxides RCrWO6 (R = Sm, Eu, Gd, and Tb). (15th September 2022) - Panda, Debendra Prasad; Yanda, Premakumar; Behera, Sinay Simanta; Sundaresan, A.
Abstract: We report new magnetic oxides R CrWO6 ( R  = Sm, Eu, Gd, and Tb) crystallizing in the polar orthorhombic structure (Space Group: Pna 21 ), where edge-shared dimers of CrO6 and WO6 octahedra are connected by sharing corners and establish a three-dimensional framework. All these compounds exhibit antiferromagnetic ordering of Cr 3+ spins at T N ∼ 28–32 K, except SmCrWO6, which shows weak ferromagnetism below T N  = 32 K. Isothermal magnetization curves of R CrWO6 ( R  = Gd and Tb) at low temperatures show field-induced metamagnetic transition. Further, a dielectric anomaly at T N in all these compounds evidences the magnetodielectric effect. In addition, GdCrWO6 demonstrates magnetocaloric effect (MCE) with a maximum magnetic entropy change of 9.22 J kg −1 K −1  at 70 kOe with relative cooling power (RCP) ∼ 101 J kg -1 . On the other hand, TbCrWO6 exhibits both conventional and inverse magnetocaloric effects with significant entropy change and RCP. Highlights: We have synthesized new polar magnets R CrWO6 ( R  = Sm, Eu, Gd, and Tb) crystallizing in the Pna 21 space group. All these compounds exhibit antiferromagnetic ordering of Cr 3+ spins, except SmCrWO6, which shows weak ferromagnetism. All compounds exhibit magnetodielectric effect. GdCrWO6 shows conventional magnetocaloric effect, whereas TbCrWO6 exhibits conventional and inverse magnetocaloric effects.